BIHAR SCIENTIFIC SOCIETY AND DEVELOPMENT OF NATIONAL SCIENCE IN COLONIAL MUZAFFARPUR, 1868-1899 - Kumar, Maniranjan; Chandra, Gautam (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The science used during British rule in India was colonial in nature. Its character was to promote colonial exploitation rather fundamental research. This exploitative character of science came to be known as 'colonial science'. The kind of relationship that developed between India and Britain due to 'colonial science' inspired Indians to learn 'national science', which could lead to the development of Indians. As a result, the Bihar Scientific Society was established in colonial Muzaffarpur by Imdad Ali on 24 May 1868. Initially, it was named as British Indian Association. The society also ran translation departments and schools. Along with this, a magazine ‘Akhbar-ul-Akhyair’ was published from the society’s own printing press. Its purpose was to criticize the actions of the government and to save people from oppression by conveying their complaints to the government. In 1872, its name was changed to Bihar Scientific Society. Its objective was to do intellectual, social and moral welfare of the people as well as to translate European scientific works in regional language and make them available to common people. French orientalist Garcin-de-Tassy has mentioned the work of society in his article. Apart from this, Bihar Scientific Society has been mentioned in Deepak Kumar's book "Science and British Raj in India, 1857-1905”, David Arnold’s book "Science, Technology and Medicine in Colonial India" and others, but there is a lack of detailed study of the Bihar Scientific Society. How the Bihar Scientific Society and its translation department, schools and magazine ‘Akhbar-ul-Akhyair’ developed 'National Science' in colonial Muzaffarpur has not been highlighted. Hence, this article examines the role of Bihar Scientific Society, its translation department, schools, and magazine ‘Akhbar-ul-Akhyair’ in developing national science